Formation of aromatics and removal of nitrogen in catalytic fast pyrolysis of sewage sludge: A study of sewage sludge and model amino acids. (15th April 2018) - Wei, Fu; Cao, Jing-Pei; Zhao, Xiao-Yan; Ren, Jie; Gu, Bo; Wei, Xian-Yong
Graphical abstract: Highlights: Amino acid was selected as the N -containing model compounds for protein-rich sewage sludge. The optimal temperature and Si/Al ratio of HZSM-5 were determined. Amino acids with aromatic ring or saturated hydrocarbon side chain favored formation of aromatics. The catalytic mechanism and nitrogen transfer behavior of sewage sludge were proposed. Abstract: To elucidate the catalytic mechanism and nitrogen transfer behavior of sewage sludge (SS) during catalytic fast pyrolysis (CFP), product distributions and nitrogen transformation from SS and amino acids during CFP were investigated on a drop tube quartz reactor at various temperatures and HZSM-5 catalysts. Phenylalanine (Phe), proline (Pro), leucine (Leu) and aspartic acid (Asp) were employed as model compounds with different chemical structures for protein-rich SS to help analyze catalytic cracking behavior of SS. During CFP of SS, the maximum aromatics yield of 16.4% was obtained over HZSM-5 with Si/Al ratio of 25 at 500 °C, and increasing temperature promoted the conversion of nitrogen to NH3 . Amino acids with aromatic ring or saturated hydrocarbon side chain such as Phe and Leu in SS favored the formation of aromatics and NH3 . Amino acids of N -ring structure in SS promoted the formation of N -containing heterocyclic compounds, which were prone to coke on catalyst and inhibited the catalytic cracking of SS to produce more aromatics and NH3 . In addition, excessive Asp of short chain dibasic acid structure in SS was not conducive to the complete thermal decomposition of SS under the optimum pyrolysis condition. A general catalytic mechanism of SS was proposed to provide support for the resource reuse of SS.